The 1990 United States Census [2nd] - United States. Bureau of the Census (Salt Lake City, UT : Project Gutenberg, 1992)
"The 1990 United States Census" by the United States Bureau of the Census is a scientific publication that presents comprehensive demographic data collected during the 1990 census, likely written in the early 1990s. This document aims to provide insights into the population characteristics of the United States, detailing various statistics related to regions, states, and demographic components such as age, race, and household types. The opening of the census report introduces the geographic regions defined according to the census, which are the Northeast, South, Midwest, and West. It includes a breakdown of the population estimates across these regions, along with specific data for individual states. Following this introduction, various tables present detailed statistics regarding the total populations, demographics such as sex and age distribution, and household information, illustrating the structured and methodical approach taken to analyze the nation$1 (Bs population. Each section is dense with numerical data, serving as a vital resource for researchers, policymakers, and anyone interested in understanding the social and demographic trends of the early 1990s. (This is an automatically generated summary.)s
Wikipedia page about this book: https://en.wikipedia.org/wiki/1990_United_States_census
Release date is 1992-08-01
Keywords: United States -- Population -- Statistics; United States -- Census; Housing -- United States -- Statistics